Public Trust in Business - Harris, Jared D.; Moriarty, Brian; Wicks, Andrew C. (Cambridge : Cambridge University Press, 2014)
Public trust in business is one of the most important but least understood issues for business leaders, public officials, employees, NGOs and other key stakeholders. This book provides much-needed thinking on the topic. Drawing on the expertise of an international array of experts from academic disciplines including business, sociology, political science and philosophy, it explores long-term strategies for building and maintaining public trust in business. The authors look to new ways of moving forward, by carefully blending the latest academic research with conclusions for future research and practice. They address core drivers of public trust, how to manage it effectively, the consequences of low public trust, and how best to address trust challenges and repair trust when it has been lost. This is a must-read for business practitioners, policy makers and students taking courses in corporate social responsibility or business ethics.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Trust; Public relations; Business ethics; Corporate culture